Electrical resistivity of bismuth implanted into silicon - Silva, Antonio Ferreira da (2014)
We investigate the electrical properties of Bi-doped Si samples, prepared by ion implantation, in a range of concentrations around and above the metal–nonmetal transition. Comparison between experimental and theoretical values of the resistivity brought out that in these samples a similar behavior is observed as for other n-doped Si, thus confirming the results obtained in the same range of impurity concentration, i.e., p(Sb)<P(p)<p(As)<p(Bi).